2017
DOI: 10.5039/agraria.v12i3a5445
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and quality of chickpea seeds in Northern Minas Gerais, Brazil

Abstract: This study evaluated the productive performance, physiological and sanitary quality of the 'BRS Cícero' chickpea cultivar seeds at two sites in the municipality of Montes Claros, MG, at different planting times under irrigated system. The production characteristics evaluated were: plant height and weight, harvest index, weight per 100 seeds and productivity. The germination, first germination count and germination speed index were used to evaluate the physiological quality of the seeds, and the freezing filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
2
10
0
5
Order By: Relevance
“…Under conditions similar to those in the present study, Hoskem et al (2017) tested the Cicero cultivar at three different sowing times (May 22 nd , June 20 th , and July 26 th ), and reported yields averaging 2.72 t ha -1 , with the best result obtained when chickpeas were sown in the month of June, with yields close to 3 t ha -1 .…”
Section: ( )supporting
confidence: 61%
See 2 more Smart Citations
“…Under conditions similar to those in the present study, Hoskem et al (2017) tested the Cicero cultivar at three different sowing times (May 22 nd , June 20 th , and July 26 th ), and reported yields averaging 2.72 t ha -1 , with the best result obtained when chickpeas were sown in the month of June, with yields close to 3 t ha -1 .…”
Section: ( )supporting
confidence: 61%
“…( + 0.5) 1 Artiaga et al (2015), assessed chickpea genotypes sown in non-irrigated land in the Midwest of Brazil from January to July, and found heights for the Cicero cultivar ranging from 33 to 57 cm, and heights for the IAC Morocco cultivar ranging from 45 to 63 cm. Hoskem et al (2017), using the Cicero cultivar, found the highest values for plant height (52 cm) in the municipality of Montes Claros-MG when chickpeas were sown in May.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…For the July 22nd sowing, the seeds harvested at 128 DAS had their germination compromised by the occurrence of rainfall near the harvest. Hoskem et al (2017), while evaluating the production and quality of Cícero chickpea seeds in the municipality of Montes Claros and São Norberto -Minas Gerais state, at different planting periods, found the maximum germination in seeds from the May 22nd sowing, with an average of 85.5%. Araújo et al (2010), comparing chickpea seed lots from different genotypes grown in the North of Minas Gerais, found their germination ranging from 33 to 73%, and also remarkable vigor differences.…”
Section: Resultsmentioning
confidence: 99%
“…According to Paula Júnior and Venzon (2007), the main form of consumption in Brazil is as whole grains cooked and served in the form of salad or pasta. According to Hoskem et al (2017), despite being a cold climate plant, the chickpea adapts well to tropical regions like Brazil, producing crops with good development and high productivity.…”
Section: Introductionmentioning
confidence: 99%